Occupational stress among workers at an oil company in Pointe-Noire, Congo-Brazzaville (International Journal of Scientific Research and Management (IJSRM), 2022)
Introduction: Work-related stress is an ongoing psychosocial risk in the workplace. The oil industry, because of its complexity, is a high-risk sector. The objective of this work was to assess the level of work stress among workers of an oil company in Congo-Brazzaville. Methods: This was a cross-sectional descriptive study conducted between July and September 2021 among a population of workers at an oil company in Pointe-Noire. Data were collected using the Perceived Stress Scale (PSS 10). Results: The study involved 203 workers. Male staff was predominant (81.3%) with an average age of 39.5 years. The calculation of PSS 10 scores revealed that 39.4% of workers experienced moderate and high stress (score greater than 14). The prevalence of stress was higher among those under 30, female workers, expatriates and those working in administrative sites (57.1%, 52.6%, 52.6% and 46% respectively). There was a significant correlation between the presence of moderate or high stress and the workplace (r=-0.17; p=0.015). Conclusion: This study showed that the employees of this oil company suffered from a state of stress whose origin may be linked to certain socio-professional factors. Prevention will result from a thorough analysis of these factors and the identification of other psychosocial factors.